Religious and spiritual beliefs and practices of patients and physicians from a tertiary care hopital in Malaysia - Rathor, Mohammad Yousuf; Abdul Rani, Mohammed Fauzi; Mohd Shah, Azarisman Shah; Omar, Ahmad Marzuki (Ibrahim Medical College, 2011)
In recent years there has been growing awareness regarding the role of religion and spirituality(R/S)in the practice of clinical medicine. Until recently, assessing patients’ R/S beliefs was viewed as superstitious and inappropriate. Now,the scenario has changed remarkably. We aim to assess the beliefs and observations of physicians regarding their role on patient’ shealth and whether they address such issues in their clincal practice. Concomitantly, we aim to assess the belief so four patients and whether they like to address such issues.